The Effect of Interest Rate Volatility, Financial Technology, and Operational Efficiency on the Profitability of Banking Sector Companies Listed on the Indonesia Stock Exchange in 2021-2024 - Sirait, Citra Oktafiani; Dimita H. P. Purba; Rike Yolanda Panjaitan; Ivo Maelina Silitonga (METHOSIKA: Jurnal Akuntansi dan Keuangan Methodist, 2026)
This study aims to examine and analyze the effect of interest rate volatility, financial technology, and operational efficiency on the profitability of banking sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used in this study is purposive sampling. The population consists of 48 banking companies, of which 21 companies were selected as samples. The data were obtained from companies listed on the Indonesia Stock Exchange through the official website www.idx.co.id. This research employs a quantitative approach with multiple linear regression analysis as the data analysis method. The results show that partially, interest rate volatility has a negative and insignificant effect on profitability. Financial technology has a positive and significant effect on profitability, while operational efficiency has a negative and insignificant effect on profitability. Simultaneously, interest rate volatility, financial technology, and operational efficiency have a significant effect on profitability. The coefficient of determination indicates that interest rate volatility, financial technology, and operational efficiency are able to explain 10.1% of the variation in profitability, while the remaining 89.9% is explained by other variables not included in the regression model.